PENGARUH PENDAPATAN ASURANSI TERHADAP DANA TABARRU’ (STUDI PADA PERUSAHAAN ASURANSI JIWA SYARIAH YANG TERDAFTAR DI OJK PERIODE 2011-2018) - Muhayati Muhayati; Budi Sudrajat (UIN Sultan Maulana Hasanuddin Banten, 2019)
Insurance income is the amount of money the company receives from the sale of insurance products. Tabarru's fund is a voluntary giving of someone to another person, without compensation, which results in the transfer of ownership of the property from the giver to another person. Aside from premium income, tabaruu funds' also come from investment returns and the accumulation of surfaru underwriting reserves for tabaruu funds' which are redistributed to tabaruu funds'. Based on the background above the formulation of the problem, namely: 1). Is there an Influence between Insurance Income and Tabaruu Funds' on Sharia Life Insurance companies registered with OJK for the period 2011-2018.2). how much influence the Insurance Revenues of the Tabaruu Fund 'on Sharia Life Insurance companies registered in the OJK for the period 2011-2018. This study aims to 1). To find out the effect of insurance income on tabaruu funds' on Sharia Life Insurance companies registered with OJK for the period 2011-2018. 2). To find out how much influence Insurance Income has on Tabaruu Funds' on Sharia Life Insurance companies registered with OJK for the period 2011-2018. This research was conducted at a life insurance company registered with OJK in September to October 2019, with quantitative research methods, testing the hypothesis using simple linear regression analysis through the test (t) with the intent to determine the effect of the independent variables on the dependent variable. It can be concluded, there is a significant effect of the value of t_ (count) of 5.689 while the value of t_ (table) obtained from the distribution table t is sought at the significance of 5%: 2 = 2.5% (two-way test) degrees of freedom (df) nk-1 or 40-1-1 = 38, we get t table of 2.02439. because the value of t_ (count)> t_ (table) = 5.689> 2.02439 with a significance level of 0.005, because the significance value is much smaller than 0.005, it can be concluded that Ho is rejected Ha is accepted. The influence derived from the coefficient of determination (R-Square) of 0.760 means that the magnitude of the effect of insurance income on tabarru funds' 76.0% while the remaining 24.0% is explained by other factors not examined in this study.